THE STUDENTS’ DISCIPLINE AND SOCIAL BEHAVIOR OF MA MIFTAHUL ULUM CERMENAN NGORO JOMBANG CORRELATION - Khudriyah Khudriyah; Azifatun Najahah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
In the process of teaching and learning, disciplinary habits can foster students' social behavior. For students who have high discipline will behave well socially wherever they are. Researchers are interested in examining the relationship of students’ discipline with social behavior of MA MiftahulUlumCermenan Ngoro Jombang. This research method is quantitative research. The results of the product moment analysis found that there was a very significant positive correlation between discipline and students' social behavior. It is known that the results of the discipline of students belonging to the low category which are 4 respondents or 7.27%, middle category there are 19 respondents or 34.55%, and classified as high category there are 32 respondents or 58.18%. While the results of the social behavior of MA students. Miftahul ‘UlumCermenan Ngoro Jombang which is in the low category there is one respondent or 1.81%, which is classified as middle category there are 21 respondents or 38.19%, and classified as high category there are 33 respondents or 60.00%. The conclusion of this study shows that there is a significant and strong relationship between discipline and social behavior of MA MiftahulUlumCermenan Ngoro Jombang students, because the hypothesis test results show that the r count of 0.841 is greater than the r table of 0.2656, and the significance value is 0.000 < 0.05.